Syrian private and public hospitals distribution roles in achieving regional development - Zedan, Rami (Latakia University Journal - Economic and Legal Sciences Series, 2018)
In general, both private and public hospitals play extremely important roles in all economic and social development paces. These hospitals contribute not only in health care, highly qualified staff supply, and supper thinking educational levels, but also in local capital investments, labor increase and unemployment limitation. Or else regional development is achieved by technology in use across the country reducing internal immigration whose effects are at their most important through the country. Attracting and localizing newly economic activities at those hospitals surrounding will result in economy growth ratio lift up and development push forward. This paper studies hospital distribution in the Syrian provinces compared with that of population, thus hospital contribution strong or weak effects on the regional development revealed. دور توزع المشافي السورية (الخاصة والعامة) في تحقيق التنمية الإقليمية تؤدي المشافي عموماً (العامة والخاصة) أدواراً تنمويةً بالغة الأهمية على كافة الأصعدة الاقتصادية والاجتماعية، سواء من خلال مساهمتها في الحفاظ على الصحة العامة ورفد المجتمع بالكوادر العلمية المؤهلة وزيادة المستوى الثقافي والفكري لأبنائه، أو من خلال توظيفها لرؤوس الأموال ومنع تسربها إلى الخارج، أو من خلال تشغيل اليد العاملة والحد من البطالة، أو بالتطوير التكنولوجي في البلد، وكذلك من خلال تحقيق التنمية الإقليمية وذلك بالحد من الهجرة الداخلية وما لذلك من آثار بالغة الأهمية على كافة مناطق البلد، هذا فضلاً عن استقطاب وتوطين أنشطة اقتصادية جديدة إلى أماكن وجود تلك المشافي أو بالقرب منها، بما يؤدي بالمحصلة إلى رفع معدلات النمو الاقتصادي وتسريع عجلة التنمية ودفعها قُدماً نحو الأمام. في بحثنا هذا سوف نتطرق إلى دراسة انتشار وتوزع المشافي في المحافظات السورية مقارنةً بانتشار وتوزع السكان، وبالتالي معرفة مدى قوة أو ضعف مساهمة المشافي في تنشيط وتفعيل التنمية الإقليمية على المحافظات السورية.